Long-term outcome of patients with systemic sclerosis requiring home parenteral nutrition. Issue 5 (October 2015) - Harrison, Elizabeth; Herrick, Ariane L.; Dibb, Martyn; McLaughlin, John T.; Lal, Simon
Summary Background & aims Patients with systemic sclerosis may develop intestinal failure requiring home parenteral nutrition. However, few outcome data have been reported. This study aimed to review the outcome of patients with systemic sclerosis receiving home parenteral nutrition. Methods Records of all patients with systemic sclerosis who commenced home parenteral nutrition, at a national intestinal failure unit were retrospectively reviewed. Disease characteristics, survival and outcome data were evaluated. Results Twenty five patients (20% male; median age: 55 years) were included over a 22-year period (37, 200 central venous catheter days). All patients had small intestinal involvement. Prior to home parenteral nutrition, 16 failed enteral feeding. Nine patients were trained to self-administer their home parenteral nutrition; carers/relatives were trained for the remainder. Cumulative survivals on home parenteral nutrition at 2, 5 and 10 years were 75%, 37%, and 23%. Sixteen patients died from causes unrelated to home parenteral nutrition. Two patients were weaned off home parenteral nutrition. Seven patients survive on home parenteral nutrition (median: 41 months; range 9–178). Central venous catheter-related complications were low; these included occlusion (0.70 episodes per 1000 central venous catheter days), sepsis (0.19 episodes per 1000 central venous catheter days) and central venous thrombosis (0.11 episodes per 1000 central venous catheter days). Conclusions This is the longest, largest reported series of patients with systemic sclerosis receiving home parenteral nutrition. It shows that home parenteral nutrition can be used safely and effectively in patients with very severe systemic sclerosis-related gastrointestinal involvement.